2012
DOI: 10.3171/2012.2.focus1223
|View full text |Cite
|
Sign up to set email alerts
|

Carotid-cavernous fistulas

Abstract: Carotid-cavernous fistulas (CCFs) are vascular shunts allowing blood to flow from the carotid artery into the cavernous sinus. The characteristic clinical features seen in patients with CCFs are the sequelae of hemodynamic dysfunction within the cavernous sinus. Once routinely treated with open surgical procedures, including carotid ligation or trapping and cavernous sinus exploration, endovascular therapy is now the treatment modality of choice in many cases. The authors provide a review of CCFs, deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
326
0
22

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 277 publications
(380 citation statements)
references
References 83 publications
3
326
0
22
Order By: Relevance
“…3,8,9 According to Ellis et al, these disorders are caused by ischemia of the retina and require urgent treatment. 1 Wang et al share that ophthalmoplegia is observed in 23-63% of cases, while disturbances in other cranial nerves are less common (17-44%), which is confirmed by the clinical presentation observed in our case. 9 CT and magnetic resonance angiography can visualize the dilated cavernous sinus and diagnose the CCF.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…3,8,9 According to Ellis et al, these disorders are caused by ischemia of the retina and require urgent treatment. 1 Wang et al share that ophthalmoplegia is observed in 23-63% of cases, while disturbances in other cranial nerves are less common (17-44%), which is confirmed by the clinical presentation observed in our case. 9 CT and magnetic resonance angiography can visualize the dilated cavernous sinus and diagnose the CCF.…”
Section: Discussionsupporting
confidence: 76%
“…1,3,7 The age of our patient and the lack of history of previous facial craniocerebral trauma are suggestive of the spontaneous nature of the CCF. The absence of clinical evidence of fi bromuscular dysplasia, EhlersDanlos syndrome and elastic pseudoxanthoma suggested the presence of an intracavernous aneurysm, but it was not visualized by neuroimaging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations